Grynfeltt-Lesshaft lumbar hernia: a rare cause of bowel obstruction misdiagnosed as a lipoma - Stupalkowska, Weronika (J Surg Case Rep, 2017)
Grynfeltt-Leschaft hernia is a type of lumbar hernia occurring in the superior lumbar triangle. Because of its rarity and non-specific presentation, lumbar hernia often poses a diagnostic challenge, and it can be easily misdiagnosed as a lipoma. If the correct diagnosis is missed, there is a significant risk of complications including hernia incarceration or strangulation. Here, we present a case of Grynfeltt-Lesshaft hernia which was repeatedly misdiagnosed as a lipoma and presented acutely with large bowel obstruction. A definite diagnosis was made by a computed tomography scan and the patient had emergency laparotomy and successful mesh repair of the hernia defect.